(untitled) (Ushuluddin International Conference (USICON), 2017)
Beside the fact that terrorism has its root in history, it appears with different expressions. In the modern era when nation state is present, at least there are four waves of terrorism: anarchist wave, anti-colonial wave, new left wave, and religious wave (Rapoport 2002). Every wave operates with its unique and distinct activities and mechanism, for terrorism is also a means to certain objectives, it always adapts its methods with the spirit of the age. Two important drives for the emergence of terrorism in the late nineteenth century are technology and the development in the field of transportation and information (Rapoport, 2002). These two factors have grown rapidly nowadays and even become the core foundation for social mechanism in this postmodern era (Baudrillard, 1995). This paper will argue that terror activities done by ISIS -with its use of high technology means, cybernetic elaborations and the play of signs and simulations, relate with the very postmodern conditions. These activities are executed not coincidentally, but designed with considerations. These advance mechanism increases the scope of terror into wider audiences across the globe with the help of new media. If it refers to something, it presents the development in the field of terrorism in the shadow of new stage of history called postmodern era.